EFFECTIVENESS OF POLICE MEMBERS IN SUKABUMI RESORT - Aam Ammar Halim; Robi Mahludin (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2022)
The author uses a qualitative and descriptive approach in this article. Data collection through participant surveys, interviews and record keeping. Use tools such as the following: interview guide, field information, and storytelling. Data validation uses triangles (method, source, and time) and is analyzed for data reduction, data presentation, and results. In this study, the aim is to solve/clarify the problems that arise in the performance of duties for police officers at Sukabumi Regency Resort, in order to improve the performance of Sukabumi Regency Resort. The work of the summer police is a very important thing that needs to be done, although the policy making and preparation of the program should be adjusted according to the local policies as well as the discipline of all the officers.